Attractiveness Difference Magnitude Affected by Context, Range, and Categorization. (January 2014) - Forsythe, Matthew; Zellner, Debra; Cogan, Elizabeth; Parker, Scott
Previous studies have shown that, when subjects view hedonically positive stimuli followed by stimuli of lesser hedonic value, their preference between the stimuli of lesser hedonic value decreases. This is hedonic condensation. In addition, its opposite, hedonic expansion, occurs when subjects view less hedonically positive stimuli followed by more hedonically positive stimuli. Experiment 1 showed both hedonic condensation and expansion in subjects who viewed pictures of unattractive and moderately attractive faces. Experiment 2 showed that, when subjects were instructed to view the stimuli as coming from two different groups, hedonic expansion but not hedonic condensation was eliminated. Experiment 3 showed that increasing the attractiveness difference between the attractive and unattractive faces eliminated all effects of context on subjects' attractiveness difference judgments. Experiment 4 showed that forcing subjects to categorize the extremely attractive and unattractive faces into the same group resulted in hedonic expansion among attractive faces but not condensation among the unattractive faces. These results suggest that, as hedonic contrast changes the hedonic values of stimuli, it also changes the attention paid to those stimuli, thereby altering the degree of preference between them. Manipulations that prevent a shift in hedonic value also block a shift in the magnitude of the preference judgments.